Proving the concept of a data broker as an emergent alternative to supra-enterprise EPR systems. - Rigby, M.J.
Electronic Patient Records systems configured into large enterprise models have become the assumed best route forward. In England, as in several other countries, this has expanded to a major meta-enterprise procurement programme. However, concerns are raised that such systems lack user ownership, and experience from other sectors shows difficulties with large enterprise systems. At a time of great change and once again shifting organizations, is this move simply building large and ponderous edifices with unstable materials? Latest software engineering research is now demonstrating the potential of an alternative model, enabling trusted information brokers to search out in real time at point of use data held in registered local and departmental systems. If successful, this could enable a new and less cumbersome paradigm. The data could move where needed whatever the service configuration. A concept demonstrator has been built set in the context of health and social care in England. It is important for all technological support to the health sector to be reviewed as new technologies emerge so as to identify and exploit new opportunities, and the results of this 3 year project show that the health record information broker route merits further investigative research.
Keywords: Electronic patient records; Enterprise systems; Information broker; Software as a service